If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x2+6x+6x+20=8
We move all terms to the left:
x2+6x+6x+20-(8)=0
We add all the numbers together, and all the variables
x^2+12x+12=0
a = 1; b = 12; c = +12;
Δ = b2-4ac
Δ = 122-4·1·12
Δ = 96
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{96}=\sqrt{16*6}=\sqrt{16}*\sqrt{6}=4\sqrt{6}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(12)-4\sqrt{6}}{2*1}=\frac{-12-4\sqrt{6}}{2} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(12)+4\sqrt{6}}{2*1}=\frac{-12+4\sqrt{6}}{2} $
| (4x+6)+(4x+5)+4x=(5x+3)+4x+4x | | 22+5x=5x+13 | | 22+x=5x+13 | | X=a^2-2a+3 | | 29+14-x=71 | | 3x-(x/4)=22 | | 38=16x-10 | | 46=6+8x | | 13+19x=146 | | -4+4(x+4=x+6 | | -4+4(x-4)=x+6 | | 4x+9=-39=-4x | | 4a=+3a-a | | (1+x)²-2x²=0 | | 6n^2-n-70=0 | | 35(8+x)=4x | | (1+x)²=x²+x² | | 8x+1,83=5,49-41÷4+1,83 | | 5(6p-3)-2=(15p-11)+5 | | 17=5k−2k= | | 2k^2-12k-32=0 | | −3(n+9)=6 | | k9+4=15 | | U=2x+17 | | 6/5x+2=206/5x+2=20 | | 7*(5x)=14 | | 4x-10=6x-5-x | | 1+i=1000^0.01 | | (1=i)^100=1000 | | (1=x)^100=1000 | | 7x+47=68 | | 4/3(2x-1)=10-4x/3 |